2008
DOI: 10.1186/1472-6750-8-53
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HIV-1 antigens in plants as potential subunit vaccines

Abstract: Background: Human immunodeficiency virus type 1 (HIV-1) has infected more than 40 million people worldwide, mainly in sub-Saharan Africa. The high prevalence of HIV-1 subtype C in southern Africa necessitates the development of cheap, effective vaccines. One means of production is the use of plants, for which a number of different techniques have been successfully developed. HIV-1 Pr55Gag is a promising HIV-1 vaccine candidate: we compared the expression of this and a truncated Gag (p17/p24) and the p24 capsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 57 publications
4
82
0
1
Order By: Relevance
“…The other chimaeric L1s did not form distinct particles, and elicited significantly weaker humoral immune responses for the same dose of protein. The L1:L2 [108][109][110][111][112][113][114][115][116][117][118][119][120] particle formation was in contrast to repeated previous expression of this and the other chimaeras in insect cells, where only loose aggregates of capsomers were formed for L1:L2 [108][109][110][111][112][113][114][115][116][117][118][119][120] [95,96].…”
Section: Papillomavirus Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…The other chimaeric L1s did not form distinct particles, and elicited significantly weaker humoral immune responses for the same dose of protein. The L1:L2 [108][109][110][111][112][113][114][115][116][117][118][119][120] particle formation was in contrast to repeated previous expression of this and the other chimaeras in insect cells, where only loose aggregates of capsomers were formed for L1:L2 [108][109][110][111][112][113][114][115][116][117][118][119][120] [95,96].…”
Section: Papillomavirus Vaccinesmentioning
confidence: 99%
“…All chimaeras were very highly expressed, with yields of up to 1.2 g/kg plant tissue. The L1 chimaera containing L2 amino acids 108-120 (L1:L2 [108][109][110][111][112][113][114][115][116][117][118][119][120] ) was the most successful candidate in that it assembled into small VLPs (~30 nm), and elicited anti-L1 and anti-L2 responses in IM immunised mice, and immune sera neutralised homologous HPV-16 and heterologous HPV-52 pseudovirions. The other chimaeric L1s did not form distinct particles, and elicited significantly weaker humoral immune responses for the same dose of protein.…”
Section: Papillomavirus Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factor in the development is to identify the most suitable vector system that will induce high levels of high purity protein production, whilst maintaining plant viability over a period of between 3 to 10 days, which is the typical incubation time for transient expression. The actual incubation time depends on the vector system employed and the heterologous protein being expressed, and needs to be optimised experimentally for each system (22,21).…”
Section: Transient Expression Involves the Somatic Introduction Of Fomentioning
confidence: 99%
“…Plant expression platform has been an alternative to conventional protein expression systems due to its ease of transformation, low initial investment, high recombinant protein expression, easy scale up and the plant expressed proteins can undergo post-translational modifications [10,11]. Earlier reports had also showed that the recombinant antigens expressed in plants could be used as subunit vaccines [7,[12][13][14]. Present study was aimed at evaluating the plant expressed recombinant E. maxima gametocyte antigen Gam82 against chicken coccidiosis using a bird challenge experiment.…”
Section: Introductionmentioning
confidence: 99%